2021
DOI: 10.21580/pjpp.v6i1.7815
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Indonesian version of the Depression Anxiety Stress Scale: Factor structure, reliability, gender, and age measurement invariance

Abstract: Measurement instruments that have satisfactory psychometric properties are needed to improve mental health research and services, especially in the effort to measure, identify, and monitor the psychological problems experienced by individuals. The purpose of this study is to examine the psychometric properties of the Indonesian version of the Depression Anxiety Stress Scale (DASS). The study involved 1,922 participants from Surabaya aged between 16 and 26. The data were obtained using the convenience sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 75 publications
2
7
0
1
Order By: Relevance
“…Here are some items asked: "I feel my mouth is dry, I experience shaking hands, I feel my life is meaningless . "Composite reliability for the depression (0.872), anxiety (0.806), stress (0.816) and psychological distress 0.917 (Mutaqqin & Ripa, 2021). (Kristiana, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Here are some items asked: "I feel my mouth is dry, I experience shaking hands, I feel my life is meaningless . "Composite reliability for the depression (0.872), anxiety (0.806), stress (0.816) and psychological distress 0.917 (Mutaqqin & Ripa, 2021). (Kristiana, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…DASS merupakan alat ukur status emosi negatif individu yang dapat dipakai pada partisipan klinis maupun non klinis (Lovibond & Lovibond, 1995). DASS 42 item versi Indonesia valid dan reliabel untuk mengukur tingkat depresi, kecemasan, dan stres pada populasi Indonesia (Muttaqin & Ripa, 2021;Widyana dkk., 2020). Properti psikometri DASS-42 Indonesia versi online dilakukan Widyana, dkk (2020) memiliki reliabilitas .954 untuk sub skala depresi, .903 untuk sub skala kecemasan, dan .917 untuk sub skala stres.…”
Section: Metodeunclassified
“…For example, González-Rivera et al (2020) research indicated a low model fit between the data and the structure of DASS-21. Other findings show that the bifactor model, by adding a new factor termed "psycho-logical distress," produces the best model fit value compared to Lovibond's original model (Bottesi et al, 2015;Henry & Crawford, 2005;Kia-Keating et al, 2018;Muttaqin & Ripa, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…The results of the DASS-21 reliability test had values ranging from .77 to .90 (Kinanth et al, 2020). In addition to Kinanthi et al (2020), psychometric evaluation has been conducted by Muttaqin and Ripa (2021), whose study showed that DASS-21 has good validity and reliability after factor analysis, composite reliability, and measurement invariance were conducted (Muttaqin & Ripa, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation